CRF(1) receptor-dependent increases in irritability-like behavior during abstinence from chronic intermittent ethanol vapor exposure - Kimbrough, Adam (Alcohol Clin Exp Res, 2017)
BACKGROUND: In humans, emotional and physical signs of withdrawal from ethanol are commonly seen. Many of these symptoms, including anxiety-like and depression-like behavior, have been characterized in animal models of ethanol dependence. One issue with several current behavioral tests that measure withdrawal in animal models is they are often not repeatable within subjects over time. Additionally, irritability, one of the most common symptoms of ethanol withdrawal in humans, has not been well characterized in animal models. The corticotropin-releasing factor (CRF)-CRF(1) receptor system has been suggested to be critical for the emergence of anxiety-like behavior in ethanol dependence, but the role of this system in irritability-like behavior has not been characterized. METHODS: The present study compared the effects of chronic intermittent ethanol vapor exposure (CIE)-induced ethanol dependence on irritability-like behavior in rats using the bottle-brush test during acute withdrawal and protracted abstinence. Rats were trained to self-administer ethanol in operant chambers and then either left in a nondependent state or made dependent via CIE. Naive, nondependent, and dependent rats were tested for irritability-like behavior in the bottle-brush test 8 h and 2 weeks into abstinence from ethanol. Separate cohorts of dependent and nondependent rats were used to examine the effect of the specific CRF(1) receptor antagonist R121919 on irritability-like behavior. RESULTS: Dependent rats exhibited escalated ethanol intake compared with their own pre-CIE baseline and nondependent rats. At both time-points of abstinence, ethanol-dependent rats exhibited increased aggressive-like responses compared with naive and nondependent rats. R121919 reduced irritability-like behavior in both dependent and nondependent rats, but dependent rats were more sensitive to R121919. CONCLUSIONS: Irritability-like behavior is a clinically relevant and reliable measure of negative emotional states that is partially mediated by activation of the CRF-CRF(1) system and remains elevated during protracted abstinence in ethanol-dependent rats.